Automated switching services - Luke Garrod; Ruochen Li; Christopher Wilson (2023)
Automated switching services have recently emerged as online intermediaries that use algorithms to facilitate consumer switching. Unlike price comparison websites, these services i) act on behalf of consumers by actively switching them to the cheapest deals, ii) typically charge consumers directly, rather than charging suppliers commission, and iii) tend to consider every supplier’s price. We offer the first theoretical analysis of such services. In an oligopoly model with imperfect price information, we characterize an equilibrium with an automated switching service, and analyze its impact on market outcomes and welfare. Among other results, we show how the service’s existence benefits all consumers, despite it only serving some consumers and charging them a fee.